Significant increase in necrotizing fasciitis in the post-COVID era: a systematic review - Suliman, Osman; Abutwaimah, Jwaan; Abutwaimah, Ahmed; Alrawi, Shdaa; Abdelrahim, Zahraa; Alamri, Zainab; Niazy, Esraa; Taher, Fawzyah; Altom, Sara; Abdelmagid, Ahmed (International Journal Of Community Medicine And Public Health, 2026)
Necrotizing fasciitis (NF) is a rapidly progressive, life-threatening soft tissue infection associated with high morbidity and mortality. The COVID-19 pandemic has significantly altered healthcare delivery and patient health profiles, potentially influencing the incidence and clinical characteristics of NF. To systematically review and analyze the reported literature on necrotizing fasciitis in the post-COVID era, with a focus on incidence, risk factors, clinical presentation, outcomes, and possible links with COVID-19 infection or its sequelae. A systematic review was conducted in accordance with the PRISMA guidelines. Major databases (PubMed, Scopus, Web of Science, and Google Scholar) were searched for studies published between January 2020 and July 2025 that reported cases or series of necrotizing fasciitis in the post-COVID period. Data regarding demographics, comorbidities, COVID-19 status, clinical features, management, and outcomes were extracted and analyzed. The review identified a notable increase in reported cases of necrotizing fasciitis in the post-COVID era, particularly among patients with a history of COVID-19 infection, diabetes mellitus, obesity, or immunosuppression. Delayed hospital presentations, atypical clinical manifestations, and higher rates of severe complications were frequently observed. Mortality remained significant despite aggressive surgical and medical management, with some studies attributing poorer outcomes to post-COVID immune dysregulation and healthcare system delays. Necrotizing fasciitis appears to have increased in frequency and severity in the post-COVID era, with COVID-19–related comorbidities and immune alterations serving as potential contributing factors. Early recognition, timely surgical intervention, and heightened clinical suspicion in post-COVID patients are crucial to improving outcomes. Further large-scale studies are needed to clarify the causal relationship and guide preventive strategies.